2019
DOI: 10.3390/ijerph17010086
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Education Practices of Health Teachers from Shanghai K-12 Schools: The Current Status, Barriers and Willingness to Teach

Abstract: China is facing challenges in both undernutrition and overnutrition, resulting from unhealthy diets. Nutrition education early in life, especially in school settings, has been reported to be effective in addressing these challenges. However, little is known about how nutrition education is delivered in schools in China. This study aimed to investigate the current status of delivering nutrition education by health teachers in Shanghai and to determine the barriers and resources that influence the teachers' prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Teachers must have adequate mastery of the subject matter to develop their own strategies to connect with students to create a positive impact [ 25 ]. Consistent with other study findings in both LMICs and high-income countries, our study participants mentioned that the training and experience they gained through the project increased their level of confidence in providing puberty and menstruation education; and this has played an important role in their interest and motivation [ 26 , 27 ]. However, some key challenges arose during our pilot that should be considered in future programming.…”
Section: Discussionsupporting
confidence: 89%
“…Teachers must have adequate mastery of the subject matter to develop their own strategies to connect with students to create a positive impact [ 25 ]. Consistent with other study findings in both LMICs and high-income countries, our study participants mentioned that the training and experience they gained through the project increased their level of confidence in providing puberty and menstruation education; and this has played an important role in their interest and motivation [ 26 , 27 ]. However, some key challenges arose during our pilot that should be considered in future programming.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings suggest that commitment at the whole school level is important, and school administrators could increase the effectiveness of the actions implemented by teachers to promote food education. The crucial role of school administrators or principals has also been demonstrated in previous studies from South Korea and China, which concluded that a school administrator's lack of priority for nutrition education or an administrator not requiring teachers to teach nutrition is a barrier to implementation (48,49) .…”
Section: Discussionmentioning
confidence: 72%
“…Several international nutrition-based organizations strongly recommend that schools adapt reliable and comprehensive nutritional program, and promote nutrition education, as well as strengthen school-home-community partnerships ( 1 ), to maximize the positive impact on the general health of a community ( 2 , 3 ). This is due to the significant impact of School Nutrition Programs (SNPs) on the eating behaviors, and health and wellbeing of school children ( 4 6 ).…”
Section: Introductionmentioning
confidence: 99%